Collagen Scaffold Application in Arthroscopic Reconstruction of Osteochondral Lesions of the Talus With Autologous Cancellous Bone Grafts. Issue 1 (24th January 2023) - Gorgun, Baris; Gamlı, Alper; Duran, Mehmet Emin; Bayram, Berhan; Ulku, Tekin Kerem; Kocaoglu, Baris
Background: Single-step all-arthroscopic techniques have gained popularity recently in the treatment of osteochondral lesions of the talus (OLT). Concomitant subchondral bone defects led surgeons to add autologous bone grafting to the surgical procedures. Collagen scaffolds have been used widely for stabilization of the reconstruction and regeneration of the articular surface. Purpose: To compare single-step all-arthroscopic treatment of OLT consisting of debridement, microfracture, autologous bone grafting, and application of fibrin sealant in 2 patient groups: with versus without collagen scaffold. Study Design: Cohort study; Level of evidence, 3. Methods: Included were 94 patients who underwent single-step all-arthroscopic treatment for OLT. Autologous bone grafting was applied to 48 patients (BG group), while autologous bone grafting plus collagen scaffold was applied to 46 patients (BG+S group). A fibrin sealant was applied to both groups. Clinical outcomes were assessed with the American Orthopaedic Foot & Ankle Society (AOFAS) score and the visual analog scale (VAS) for pain. Radiological outcomes were evaluated with the magnetic resonance observation of cartilage repair tissue score. The mean follow-up time was 69.3 ± 20.7 months. Results: Patients in both groups showed statistically significant improvement in pre- to postoperative AOFAS and VAS scores ( P < .001 for all), with no difference between groups in AOFAS and VAS score improvement. Complete healing with or without hypertrophy was achieved in 42 patients in the BG group (87.5%) and 38 patients in the BG+S group (82.6%). Conclusion: The treatment of bone lesions in OLT may be the ultimate goal to obtain successful outcomes, in which case using a collagen scaffold besides grafting may not affect clinical and radiological outcomes.